Salomon Greiwer i Warsztaty Miejskie w Bochni - Swałtek-Niewińska, Dagmara (Zagłada Żydów. Studia i Materiały, 2016)
The municipal authorities in Bochnia created in 1941 workshops in the town, in order to employ Jews and produce the goods on request of the German authorities. The manager and chief organizer was Solomon Greiwer. The article is focused on the functioning of workshops, and on their impact on the fate of Jews from the Bochnia ghetto.